Preventive Effects of Citrus unshiu Peel Extracts on Bone and Lipid Metabolism in OVX Rats - Lim, Dong Wook (Molecules, 2014)
Dried Citrus unshiu peel has been widely used for various medicinal purposes in Oriental Medicine. This study evaluated the metabolic effects of dried C. unshiu peel in ovariectomized (OVX) rats. The OVX rats were divided into five groups treated with distilled water, 17β-estradiol (E2 10 μg/kg, once daily, i.p.) and dried C. unshiu peel extracts (DCPE 30, 100 and 300 mg/kg, once daily, p.o.) for eight weeks. The treatments with high-dose DCPE significantly decreased the bone mineral density (BMD) loss in the femur, which was reflected by the decrease in alkaline phosphatase (ALP), telopeptides of collagen type I (CTx) and osteocalcin (OC) serum levels. It also inhibited the increase in lipoprotein levels compared to the OVX-control group without elevating the serum levels of estradiol, aspartate aminotransferase (AST) and alanine transaminase (ALT). Furthermore, DCPE exhibits a hepatoprotective effect in OVX-induced hepatic steatosis, indicated by reduced hepatic lipid contents. Taken together, our findings suggest that DCPE has the potential to improve both lipid and bone metabolism without influencing hormones such as estrogen in OVX rats.